TCP Traffic Management to Improve Fault Tolerance and Database Security - Kutsman, Vladyslav (Archives of Business Research, 2025)
The work of any application is associated with data processing. Very often, the best way to store data is to use relational databases, which allow you to store data in a normalized, easy-to-understand form. Also very important is the ability to work with the database via an Internet connection. At the level of the DMS (database management system) itself, there are many tools for managing both the DMS itself and the users who connect to this DB, but in the process of work there is a need for additional database management in case a specific DMS has failed due to an error or there is a need to manage connections to the DB that may seem suspicious from a security point of view, for example, ddos, exceeding the connection limit, etc. This article present the architectural approach to managing the DMS, which allows you to increase the security of the system, increasing availability and creates additional control over connections to the DB.